Post-synthesis Tellurium Doping Induced Mirror Twin Boundaries in Monolayer Molybdenum Disulfide - Xujing Ji; Manjunath Nallappagari Krishnamurthy; Danhui Lv; Jixue Li; Chuanhong Jin (Applied Sciences, 2020)
Mirror twin boundaries (MTBs) have brought intriguing one-dimensional physics into the host 2D crystal. In this letter, we reported a chalcogen atom exchange route to induce MTBs into as-formed MoS2 monolayers via post-synthesis tellurium doping. Results from annular dark-field scanning transition electron microscope (ADF-STEM) characterizations revealed that tellurium substituted the sulfur sublattices of MoS2 preferentially around the edge areas. A large number of MTBs in a configuration of 4|4P-Te was induced therein. Analysis of the lattice structures around MTBs revealed that such a tellurium-substitution-induced MTB formation is an energy-favored process to reduce the strain upon a high ratio of tellurium doping.